Acute corticosteroid-induced rhabdomyolysis in a golf player - Janse van Rensburg, D; Theron, W; Grant, T; Zondi, P; Grant, C (South African Journal of Sports Medicine, 2012)
Acute corticosteroid-induced rhabdomyolysis is a rare, but potentially life-threatening, condition that deserves the attention of medical professionals and sport scientists. Early diagnosis is vital in minimising the secondary damage caused by rhabdomyolysis. This case of rhabdomyolysis highlights the severity of symptoms and the importance of decisive treatment. Clinicians should be familiar with the most common symptoms of acute corticosteroid-induced rhabdomyolysis to enable early diagnosis and efficient management of this condition.